Pengaruh Pelatihan Dan Sistem Manajemen (K3) Terhadap Produktivitas Kerja Anggota Pada Dinas Pemadam Kebakaran Kota Tebing Tinggi - Yenni Mariani Sinurat (Economic Development Progress, 2026)
This study aims to analyze the influence of training and the occupational safety and health management system (K3) on the work productivity of members of the Fire and Rescue Department of Tebing Tinggi City. The research is motivated by the high intensity of operational activities alongside persistent challenges related to personnel competence, low participation in training programs, and increasing cases of work-related accidents. This study employs a quantitative approach with an explanatory research design. The population consists of 50 operational members, all of whom were selected as the sample using a total sampling technique. Primary data were collected through Likert-scale questionnaires and analyzed using multiple linear regression with the assistance of SPSS software. The findings reveal that training has a positive and significant effect on work productivity. Likewise, the occupational safety and health management system also exhibits a positive and significant influence on productivity. Furthermore, training and the K3 management system simultaneously show a significant effect on the work productivity of the department’s personnel. These results indicate that enhancing the quality of training and strengthening the implementation of the K3 management system should be prioritized as strategic efforts to improve sustainable work productivity.